Current state of developing advanced therapies for rare diseases in the European Union. (2nd October 2020) - Qiu, Tingting; Wang, Yitong; Dabbous, Monique; Hanna, Eve; Han, Ru; Liang, Shuyao; Toumi, Mondher
ABSTRACT: Objective: Advanced Therapy Medicinal Products (ATMPs) present significant therapeutic advantages for inherited rare diseases. However, the development of orphan ATMPs is challenging due to their complexity and unpredictable biological activity. This study aims to comprehensively describe the current state of orphan ATMPs in Europe. Methods: Orphan drugs (ODs) granted by European Commission until March 2020 were investigated. The characteristic of diseases and ATMPs were extracted from the public summary reports of ODs from Committee for Orphan Medicinal Products. The methodology for the pivotal studies of ATMPs was extracted. Results: A total of 274 ATMPs were identified, covering 116 rare diseases, with metabolic, optical, and oncologic diseases being the most targeted. A total of 158 ATMPs were indicated for life-threatening diseases, 129 ATMPs targeted diseases currently lacking authorized or satisfactory treatment available. Twenty-eight ATMPs are being investigated in the phase II/IIII or phase III studies. The median patient size of pivotal studies was 127, 15 were open-label studies, 8 were single-arm trials, and 14 reported surrogate outcomes. Conclusion: There are rapid growths in developing ATMPs for life-threatening diseases with high unmet clinical needs. Optimizing the study methodology and exploring innovative design to facilitate the market access is paramount.